Pengembangan Mobile Learning Sebagai Media Pembelajaran Sistem Digital di Pendidikan Tinggi - Dewa Ayu Kadek Pramita; Anak Agung Gde Ekayana (Journal of Innovative and Creativity, 2026)
Learning in Digital Systems courses at the higher education level still faces challenges related to the limited availability of interactive learning media that are not yet able to fully facilitate students’ active engagement in constructing understanding of abstract and complex concepts. This condition has an impact on low learning participation and suboptimal achievement of students’ conceptual understanding. Therefore, the development of innovative learning media aligned with constructivist learning theory is necessary, emphasizing students’ active roles in independently and meaningfully constructing knowledge through interaction with the learning environment. This study aims to develop Interactive Mobile Learning (M-Learning) as an alternative learning medium for Digital Systems courses that supports mobile technology–based instructional innovation in higher education. The research employed the ADDIE development model, which consists of needs analysis, design, development, implementation, and evaluation stages. The resulting product is a mobile-based interactive M-Learning application containing learning materials, simulations, practice exercises, and learning evaluations designed to enhance interaction and students’ learning autonomy. Media evaluation involved lecturers and students from the Institute of Business and Technology Indonesia through questionnaires and tests to assess validity, reliability, feasibility, and effectiveness. The results indicate that the developed Interactive M-Learning is valid and feasible for use and is capable of improving students’ conceptual understanding and engagement in digital systems learning.